2019
DOI: 10.1007/s42330-019-00067-5
|View full text |Cite
|
Sign up to set email alerts
|

Context Variation and Syntax Nuances of the Equal Sign in Elementary School Mathematics

Abstract: Existing research suggests that young children can develop a partial understanding of the equal sign as an operator rather than as a relational symbol of equivalence. This partial understanding can be the result of overemphasis on canonical equation syntaxes of the type a + b = c in elementary school mathematics. This paper presents an examination of context and syntax nuances of relevant sections from the grade 1 Greek series of textbooks and workbooks. Using a conceptual framework of context variation, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Insufficient understanding of AE may affect the learning of this next stage more negatively. Studies have shown that students generally try to reach the result in the given equality rather than understanding the meaning of the "equality" sign (Stephens et al, 2013;Voutsina, 2019). It can be said that both the language used by the teachers and the language in the textbooks are effective in the writing of the same type of VE.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient understanding of AE may affect the learning of this next stage more negatively. Studies have shown that students generally try to reach the result in the given equality rather than understanding the meaning of the "equality" sign (Stephens et al, 2013;Voutsina, 2019). It can be said that both the language used by the teachers and the language in the textbooks are effective in the writing of the same type of VE.…”
Section: Discussionmentioning
confidence: 99%
“…With eons now on my radar, I would also come to learn that the publication of special issues disrupts the regularly scheduled publication of regular submissions. For example, there are no English language mathematics education articles in 17(1), 17(2) is a special issue, 17(3) houses many math education articles (e.g., Francis et al, 2017;Hyslop-Margison et al, 2017;Pyper, 2017;Towers et al, 2017), and Watson and English (2017) is the only English language math education article in 17(4). Each of these articles, which came to me at different times and took varying amounts of time to get published, represents the ebbs and flows of the journal and the role of special issues, which finally started to make a bit more sense.…”
Section: Sincerely Eganmentioning
confidence: 99%
“…By the end of the year, I had handled 36 more. Of those 36 manuscripts, a few made their way into the pages of issue 19 (3)—e.g., Takeuchi et al ( 2019 )—and issue 19 (4)—e.g., Voutsina ( 2019 ), and Coles and Sinclair ( 2019 ). The accepted articles, I remember; I would not be able to recall details about the 33 manuscripts that were rejected that year quite as quickly.…”
Section: The Springer Era (2018–present)mentioning
confidence: 99%